Slang Words in Blackbear’s Song Lyrics from Cybersex Album - Yudi, YudiJanuarsandi; I Dewa Ayu Devi Maharani Santika; I Komang Sulatra (Institut Pariwisata dan Bisnis Internasional, 2025)
Slang words are non-standard vocabulary either spoken or written. Generally, slang words are spoken by a group of people informally. The goals of this research are to discover the types of slang words and the process of creating slang words found in Blackbear's song lyrics from the Cybersex album. The observation method was used in collecting the data in this study. The descriptive qualitative method was used to analyze the data. Based on the data there were two theories used in analyzing the data, first is theory by Champman (2007) to analyze the types of slang word and theory by Yule (1985) to analyze the process of creating slang word. The result of this study shows that 76% of primary slang and 24% data of secondary slang. In the process of creating slang, this study found 6 types from 9 types process of creating slang, there are blending, clipping, coinage, compounding, acronym, and borrowing.